The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/chem.202103491
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bromine Fused Salts Based on Quaternary Ammonium Molecules and Their Relevance for Use in a Hydrogen Bromine Redox Flow Battery

Abstract: Bromine complexing agents (BCA) in aqueous electrolytes for hydrogen bromine flow batteries are used to reduce bromine‘s vapour pressure, while an insoluble and liquid fused salt is formed. The properties (concentrations, composition, conductivity and viscosity) of this fused salt are investigated in this study systematically ex situ by using 7 BCAs at different state of charge in HBr/Br2/H2O electrolytes with a theoretical capacity of 179.6 Ah L−1. Bromine is stored in the fused salt at concentrations up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Thus, we conclude that 3-MBPy shows significantly stronger binding with bromine than MEP. This is expected because 3-MBPy has a longer alkyl side chain than MEP (butyl vs. ethyl); 40 however to our knowledge this is the first characterization of the aqueous phase bromine concentration of emulsive battery electrolytes using 3-MBPy. We further consider the low aqueous-phase concentration of bromine obtained when using 3-MBPy to be promising towards reduced zinc corrosion during battery cycling and enhanced coulombic efficiency.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, we conclude that 3-MBPy shows significantly stronger binding with bromine than MEP. This is expected because 3-MBPy has a longer alkyl side chain than MEP (butyl vs. ethyl); 40 however to our knowledge this is the first characterization of the aqueous phase bromine concentration of emulsive battery electrolytes using 3-MBPy. We further consider the low aqueous-phase concentration of bromine obtained when using 3-MBPy to be promising towards reduced zinc corrosion during battery cycling and enhanced coulombic efficiency.…”
Section: Resultsmentioning
confidence: 85%
“…21 As a result, the viscosity of the polybromide phase decreases with the increasing initial Br 2 concentration and the difference between the 3-MBPy polybromide phase and the MEP polybromide phase diminishes. 40 In battery applications, electrolyte ionic conductivity is an important parameter which often determines battery Ohmic losses and has a strong impact on voltage efficiency. For ex situ conductivity measurements, shown in Fig.…”
mentioning
confidence: 99%
“…Hydrogen (H 2 ) is used as a reducing agent combined with halogen (oxidizer) dissolution aqueous solution in the ARFB system. 63 Therefore, Cl 2 and Br 2 are most promising to use in such RFB systems as their standard potentials of the corresponding redox couples are the highest (1.36 V for Cl 2 /Cl − , and 1.09 V for Br 2 /Br − ). For the Hydrogen-Halogen RFB, the reactions are as follows (X representative halogen): As the reaction equation shows, the protons are transferred from the anode through the membrane into the electrolyte with the charge/discharge.…”
Section: Hydrogen-halogen Redox Flow Batterymentioning
confidence: 99%
“…64 The bromine vapor pressure variation, the insoluble matter storage halogen, and the solid material form show the bromine high concentrations (13.6 M) stored in the fused salt, with the theoretical energy capacity rushing up to 730 Ah L −1 . 63,65 Recently, it was found that the hydrogen-bromine RFB (HBRFB) possesses higher specific power with a voltage efficiency of more than 90% and higher solubility in an aqueous solution, and is an interesting subject for research. In typical HBRFB systems, Pt catalysts are often used as electrode materials (Fig.…”
Section: Hydrogen-halogen Redox Flow Batterymentioning
confidence: 99%
“…This issue can be minimized by employing bromine capturing agents (BCA) such as 1-ethylpyridinium bromide, 1-alkylpyridin-1-ium bromides, and 1-alkyl-3-methylimidazol-1-ium bromides to suppress the vapor pressure of bromine. [49][50][51] Yet, the strong interaction between BCA and anionic groups in the proton exchange membrane decreases the proton conductivity as it reduces the voltage efficiency of the system. Moreover, crossover of Br À /Br 3 À species results in the degradation of the hydrogen oxidation/evaluation catalyst.…”
Section: H 2 /Mn Redox Couplementioning
confidence: 99%